The geography of talent development - Hancock, David J.; Vierimaa, Matthew; Newman, Ashley (Frontiers in Sports and Active Living, 2022)
Geography (i.e., birthplace) is one of many factors that influence talent development. When one’s birthplace leads to advantages in sport participation or performance, it is called a birthplace effect. Nearly two decades of committed research has revealed that birthplace effects are pervasive across sports and countries. Recently, researchers have attempted to better understand birthplace effects by considering various metrics that serve as proxies for birth advantages; for instance, population size, population density, and proximity to sport clubs. Underlying mechanisms that explain birthplace effects include infrastructure (e.g., environment and facilities) and social structure (e.g., family and safety), though contextual differences across existing research (e.g., sports and countries) make it difficult to fully explain the effects. Herein, we provide more depth regarding these elements of birthplace effects, while also presenting new data on “talent hotspots”; that is, communities with optimal population and density for talent development.